Teff could contribute to the Sustainable Goals of United Nation’s Goals in low-income areas of Middle East and North Africa - Golmohamadi, Amir; Yazdi, Reyhaneh Akbar Nejad; Kita, Kenna (Open Science Journal, 2020)
<span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Several Sustainable Development Goals of the United Nation are directly or indirectly related to nutrition, including SDG1 (no poverty) and SDG2 (zero hunger). Many parts of the Middle East and North Africa (MENA) region are experiencing poverty or suffering from micronutrient (Calcium, Iron, and Vitamin D) deficiencies, which has contributed to a high mortality rate among children and pregnant women. Teff, an old and well-known grain in MENA and a “Super Grain” in developed countries, has a strong potential to be utilized in food product development activities in MENA. These new products can be produced by local scientists and be sold domestically or internationally. The aim of this short communication is to review the limitations and opportunities that exist in the process of food product development with Teff. <span style="font-size: 12.0pt; line-height: 150%; font-family: 'Times New Roman',serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; background: white; mso-highlight: white;">Several Sustainable Development Goals of the United Nation are directly or indirectly related to nutrition, including SDG1 (no poverty) and SDG2 (zero hunger). Many parts of the Middle East and North Africa (MENA) region are experiencing poverty or suffering from micronutrient (Calcium, Iron, and Vitamin D) deficiencies, which has contributed to a high mortality rate among children and pregnant women. Teff, an old and well-known grain in MENA and a “Super Grain” in developed countries, has a strong potential to be utilized in food product development activities in MENA. These new products can be produced by local scientists and be sold domestically or internationally. The aim of this short communication is to review the limitations and opportunities that exist in the process of food product development with Teff.